2013
DOI: 10.1373/clinchem.2012.194381
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Effects on Driving Skills

Abstract: BACKGROUND Cannabis is the most prevalent illicit drug identified in impaired drivers. The effects of cannabis on driving continue to be debated, making prosecution and legislation difficult. Historically, delays in sample collection, evaluating the inactive Δ9-tetrahydrocannabinol (THC) metabolite 11-nor-9-carboxy-THC, and polydrug use have complicated epidemiologic evaluations of driver impairment after cannabis use. CONTENT We review and evaluate the current literature on cannabis’ effects on driving, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
380
0
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 513 publications
(394 citation statements)
references
References 67 publications
4
380
0
10
Order By: Relevance
“…2), similar to the window of acute intoxication (40 ). A higher 5-g/L cutoff results in a short detection window for occasional to moderate smokers-shorter than impairment windows (5,40 )-emphasizing the challenge in establishing appropriate science-based per se cannabis drugged driving legislation. Role of Sponsor: NHTSA played a direct role in the design of the study and review and interpretation of data.…”
Section: Continued On Page 866mentioning
confidence: 99%
“…2), similar to the window of acute intoxication (40 ). A higher 5-g/L cutoff results in a short detection window for occasional to moderate smokers-shorter than impairment windows (5,40 )-emphasizing the challenge in establishing appropriate science-based per se cannabis drugged driving legislation. Role of Sponsor: NHTSA played a direct role in the design of the study and review and interpretation of data.…”
Section: Continued On Page 866mentioning
confidence: 99%
“…Not surprisingly, roadside surveys have demonstrated that driving under the influence of cannabis (DUIC) is a common and widespread occurrence [2][3][4][5]. Cannabis consumption has been shown to have impairing effects on cognitive functions and psychomotor skills related to driving and to be associated with an elevated accident risk [6][7][8][9]. Thus, DUIC has severe implications on global road safety and is considered a serious criminal offense in many countries [10].…”
Section: Introductionmentioning
confidence: 99%
“…16 Debate exists regarding the extent to which driving under the influence of cannabis causes motor vehicle fatalities. [17][18][19][20][21] In Ontario in 2015, 12% of grade 7-12 students rode with a driver who had used drugs, including cannabis, at least once in the previous year. 22 In light of the impending legalization of cannabis in Canada, we aimed to determine what individual and area-level characteristics are associated with risky driving and passenger behaviours among grade 9-12 students in Canada.…”
mentioning
confidence: 99%